Metaproteomics and ultrastructure characterization of Komagataeibacter spp. involved in high-acid spirit vinegar production. (May 2016) - Andrés-Barrao, Cristina; Saad, Maged M.; Cabello Ferrete, Elena; Bravo, Daniel; Chappuis, Marie-Luise; Ortega Pérez, Ruben; Junier, Pilar; Perret, Xavier; Barja, François
Abstract: Acetic acid bacteria (AAB) are widespread microorganisms in nature, extensively used in food industry to transform alcohols and sugar alcohols into their corresponding organic acids. Specialized strains are used in the production of vinegar through the oxidative transformation of ethanol into acetic acid. The main AAB involved in the production of high-acid vinegars using the submerged fermentation method belong to the genus Komagataeibacter, characterized by their higher ADH stability and activity, and higher acetic acid resistance (15–20%), compared to other AAB. In this work, the bacteria involved in the production of high-acid spirit vinegar through a spontaneous acetic acid fermentation process was studied. The analysis using a culture-independent approach revealed a homogeneous bacterial population involved in the process, identified as Komagataeibacter spp. Differentially expressed proteins during acetic acid fermentation were investigated by using 2D-DIGE and mass spectrometry. Most of these proteins were functionally related to stress response, the TCA cycle and different metabolic processes. In addition, scanning and transmission electron microscopy and specific staining of polysaccharide SDS-PAGE gels confirmed that Komagataeibacter spp. lacked the characteristic polysaccharide layer surrounding the outer membrane that has been previously reported to have an important role in acetic acid resistance in the genus Acetobacter . Highlights: Komagataeibacter spp. is involved in the current high-acid acetic acid fermentation. TCA cycle enzymes were highly induced during the process. Ketol-acid redutoisomerase (ilvC) showed the highest induction during the process. Branched-chain amino acids (BCAA) must have an important role in acid resistance. Komagataeibacter spp. do not synthetize capsular polysaccharides nor LPS O-antigen.